ORGANIZATIONAL AND ECONOMIC PECULIARITIES OF PRODUCTION OF BUILDING MATERIALS FROM THE POINT OF VIEW OF INNOVATION (Marketing Journal, 2025)
The article discusses the prospects for further development of the building materials industry in the Bukhara region. The issue of the need to develop a strategy for its development, the possibility of modernization and construction of enterprises of this sector with its help, was also considered.
Keywords: investment process; construction materials; innovation; production strategies; capital construction mixtures; dynamics